High-performance asymmetric supercapacitors based on cobalt chloride carbonate hydroxide nanowire arrays and activated carbon. (20th April 2016) - Wu, Dong; Xiao, Ting; Tan, Xinyu; Xiang, Peng; Jiang, Lihua; Kang, Zhe; Tan, Pin
Abstract: Cobalt chloride carbonate hydroxide nanowire arrays (CCCH NWAs) with an average length of ∼8 μm grown on Ni foam was successfully fabricated via a simple hydrothermal process. Electrochemical tests show a specific capacitance as high as 1737 F/g at 2.5 mA/cm 2, and an good cycling stability demonstrated by a 87.3% capacitance retention after 2000 cycles at a current of 7.5 mA/cm 2 . An asymmetric supercapacitor was also successfully assembled with CCCH NWAs and activated carbon (AC) applied as positive and negative electrode, respectively. The asymmetric supercapacitor exhibited a maximum energy density of 29.1 Wh/kg at power density of 100 W/kg in the wide voltage region of 0–1.6 V, as well as a good electrochemical stability. The impressive results presented here may pave the way for promising applications in cheap, easy preparation and high energy density storage systems.